Smoothed monthly Greenland ice sheet elevation changes during 2003–2023 - S. A. Khan; H. Seroussi; M. Morlighem; W. Colgan; V. Helm; G. Cheng; D. Berg; V. R. Barletta; N. K. Larsen; W. Kochtitzky; M. van den Broeke; K. H. Kjær; et al. (Earth System Science Data, 2025)
The surface elevation of the Greenland Ice Sheet is constantly changing due to the interplay between surface mass balance processes and ice dynamics, each exhibiting distinct spatiotemporal patterns. Here, we employ satellite and airborne altimetry data with fine spatial (1 km) and temporal (monthly) resolutions to document this spatiotemporal evolution from January 2003 to August 2023. To estimate elevation changes of the Greenland Ice Sheet (GIS), we utilize radar altimetry data from CryoSat-2 and EnviSat, laser altimetry data from the ICESat and ICESat-2, and laser altimetry data from NASA's Operation IceBridge Airborne Topographic Mapper. We produce continuous monthly ice surface elevation changes from January 2003 to August 2023 on a 1 km grid covering the entire GIS. We estimate cumulative ice loss of 4352 Gt ± 315 Gt (12.1±0.9 mm sea level equivalent) during this period, excluding peripheral glaciers. Between 2003 and 2023, the ice sheet land-terminating margin underwent a significant cumulative thinning of several meters. Ocean-terminating glaciers exhibited thinning between 20–40 m, with Jakobshavn Isbræ experiencing an exceptional thinning of nearly 70 m. This dataset of fine-resolution altimetry data in both space and time will support studies of ice mass loss and will be useful for GIS modeling. To validate our monthly mass changes of the Greenland ice sheet, we use mass change from satellite gravimetry and mass change from the input–output method. On multiannual timescales, there is a strong correlation between the time series, with R values ranging from 0.88 to 0.92 (https://doi.org/10.5061/dryad.s4mw6m9dh, Khan et al., 2025)